A CO-INTEGRATION APPROACH TO UNDERSTANDING THE IMPACT OF CAPITAL STRUCTURE ON PERFORMANCE OF COMMERCIIAL BANKS’ IN NIGERIA - Kingsley Nwagu (IJRDO - Journal of Business Management, 2020)
This study was carried out to empirically examine impact of capital on profitability of commercial banks in Nigeria employing a co-integration approach. Data set used for analysis in this study was extracted from Central Bank Statistical Bulletin of 2019. This study employed, total debt and total equity as proxies for capital structure while Net profit of commercial banks in Nigeria within the scope of this study was adopted as a measure of the performance of commercial banks in Nigeria. Ex-post facto research design was adopted. Data were analyzed by employing ordinary least square regression (OLS) model on a sample of 14 commercial banks in Nigeria from 2008 through 2019; the study found that capital structure positively and significantly impacted net profit of commercial bank in Nigeria within the period under review. These findings were consistent with trade-off theory of capital structure. Following these findings, the study recommended that since equity accounted for more profit of banks in Nigeria than debt, commercial banks should employ high equity-to-debt ratio in their operations in order to reduce bankruptcy risk and reduce the high gearing associated with banking business and enhance net profit.